Visual Attention Segmentation of Genshin Impact Characters: An Eye-Tracking and Hierarchical Clustering Analysis of First-Time Players - Farhan Atriza Siregar; Rico Maykel Erawanto; Ranvika Adityansah; Randy Alexandros Purba; Dennis Jusuf Ziegel; Evta Indra (Program Studi Sistem Informasi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Raden Fatah Palembang, 2025)
This study investigates the visual attention patterns of first-time players toward character designs in anime-style role-playing games, using Genshin Impact as the research context. An eye-tracking experiment was conducted with 60 participants to capture gaze behavior during exposure to four-character stimuli. The analysis focused on heatmaps, dwell time, and first fixation points, consistently revealing a dominant focus on the character’s body region, regardless of character type or visual variation. Hierarchical clustering further segmented participants into three distinct gaze profiles: lateral scanning, peripheral attention to symbolic elements, and centralized body-centric focus. These findings underscore the importance of adaptive character design strategies that prioritize the body region for conveying emotional and narrative cues while enhancing peripheral elements to improve engagement. The study contributes to the fields of game user experience and visual attention research by integrating eye-tracking data with clustering techniques, offering actionable insights for game developers and interface designers.